Nighttime climate warming enhances inhibitory effects of atmospheric nitrogen deposition on the success of invasive Solidago canadensis - Wang, Zu-Xing; He, Zheng-Sheng; He, Wei-Ming (Climatic change, 2021)
While the individual effects of climate warming, nitrogen (N) deposition, and native plant diversity on plant invasion success are well studied, little is known about how they interact to influence this success. Here, we select invasive Solidago canadensis and four native plant species ( Digitaria sanguinalis , Echinochloa crusgalli , Pennisetum alopecuroides , and Polygonum lapathifolium ) to assemble five classes of plant communities, each of which is subject to one of the eight treatments consisting of warming and N-addition. Native plants benefit from warming or N-addition more than invasive S. canadensis , and this asymmetry causes warming or N-addition to decrease S. canadensis relative abundance. The inhibitory effect of N-addition on S. canadensis abundance is substantially enhanced by nighttime warming but not by daytime or diurnal warming. The abundance of S. canadensis varies with native plant identity rather than richness, and native plant identity and richness mediate the effects of warming and N-addition. These findings suggest that temperature- and N-dependent asymmetries in growth between invasive and native plants may comprise a mechanism underlying invasion success. This work implies that climate warming and N deposition both could decrease the success of invasive S. canadensis through enhancing invasion resistance, which is contrary to what is often thought.